Occupational pesticide exposure and safety assessment among farmers in Hohoe municipality: An ethnographic qualitative study - Forgive Awo Norvivor; Elijah Kwasi Peprah; Doreen Danso; Obed Woani Konutse (PLoS ONE, 2025)
Introduction Occupational pesticide exposure poses significant health risks, particularly among smallholder farmers in developing countries like Ghana, where such exposures are common due to widespread subsistence agricultural activities. The Environmental Protection Agency (EPA) of Ghana is responsible for registering and monitoring pesticide use and regulating the presence of unregistered or banned products on the local market; however, this regulation is ineffective. Farmers frequently acquire pesticides directly from vendors who may not possess sufficient training, and the lack of stringent measures facilitates the accessibility of hazardous products. Furthermore, while regulations mandate safe handling and disposal practices, there are also possible oversights at the community level, leaving farmers largely dependent on their own knowledge, practices, or what they have learnt from other colleagues. This study explores the safety practices, perceived exposure levels, and awareness among rural farmers in the Hohoe municipality of Ghana. Methods A qualitative ethnographic approach was adopted, involving in-depth interviews with 13 purposively selected farmers with over five years of farming experience. Data was collected using semi-structured interviews guide informed by prior literature. Thematic analysis was conducted using ATLAS.ti version 25, with open and selective coding techniques. Results Four major themes emerged: knowledge and practices of pesticide use, health risks and exposure, safety practices, pesticide storage and disposal. Most farmers (approximately 10 out of 13) reported using Glyphosate as their primary herbicide, followed by Paraquat Dichloride and 2,4-D, relying on vendor recommendations for application methods. Common health complaints included eye and skin irritation, waist pain, and temporary vision loss. While some farmers used PPE like boots and gloves, many lacked complete protective gear, especially eye protection. Pesticide containers were often stored at home or discarded on farms or by burning, indicating poor disposal practices. Awareness of pesticide expiry dates and proper dosage was inconsistent. Conclusion The study reveals substantial gaps in pesticide safety knowledge and practices among rural farmers, posing significant public health risks. Targeted interventions, including regular training on safe pesticide handling, PPE use, and environmentally sound disposal methods, are critical to reducing occupational exposure and its associated health burdens.